Completing One’s Studies as a Social Process: The Experiences of Master’s Students in Coping With Various Life Challenges - Hasyyati, Dian Suci; Hidir, Achmad; Marnelly, T. Romi (Empiricism Journal, 2026)
Completion of a master’s degree program is determined not only by students’ academic abilities but is also influenced by various social demands that accompany their lives. This study aims to understand the experiences of master’s students in the Sociology program at the University of Riau as they navigate the process of completing their studies and to identify the dynamics of the interaction between personal and environmental factors that influence their academic journey. The study employed a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The research informants consisted of nine Master’s students in Sociology who were in the process of completing their studies, as well as supporting informants from the program administration and academic advisors. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the completion of studies is a social process that takes place amid the interplay of various life demands. At the personal level, students face challenges such as fluctuations in motivation, psychological conditions, academic readiness, and time management skills. At the same time, on the environmental level students are faced with obligations of job, family duties, and the involvement in a range of social activities. The research results show that the experience of doing one’s studies cannot be understood solely as an individual matter or solely as the consequence of external factors, but as a consequence of an interaction of students’ personal capacities and the different social structures around them. This study contributes to enriching the field of sociology of higher education by demonstrating that the completion of graduate studies is a complex and multidimensional social process. The research findings also provide an empirical basis for strengthening academic support systems that are more responsive to students’ needs and experiences.